Film thickness and friction of ZDDP tribofilms - Dawczyk,J; Morgan,N; Russo,J; Spikes,H (Tribology Letters, 2019)
Tribofilm formation by several zinc dialkyl- and diaryldithiophosphate (ZDDP) solutions in thin film rolling-sliding conditions has been investigated. A primary, a secondary alkyl and a mixed alkyl ZDDP show similar rates of film formation and generate films typically 150 nm thick. Another secondary ZDDP forms a tribofilm much faster and the film is partially lost after extended rubbing. An aryl ZDDP forms a tribofilm much more slowly. The films all have a pad-like structure, characterised by flat pad regions separated by deep valleys. Three different techniques have been used to analyse the thickness and morphology of the tribofilms: spacer layer imaging (SLIM), scanning white light interferometry (SWLI) of the gold-coated film and contact mode atomic force microscopy (AFM). The SLIM method measures considerably thicker films than the other two techniques, probably because of lack of full conformity of a glass disc loaded against the rough tribofilm. No evidence of a highly viscous layer on top of the solid tribofilm is seen. SWLI and contact mode AFM measure similar film thicknesses. The importance of coating the tribofilm with a reflective layer prior to using SWLI is confirmed. As noted in previous work, the formation of a ZDDP tribofilm is accompanied by a marked shift in the Stribeck friction curve towards higher entrainment speed. For a given ZDDP this shift is found to correlate with the measured tribofilm roughness, proving that it results from the influence of this roughness on fluid entrainment in the inlet.